Streptococcus suis meningitis complicated with communicating hydrocephalus: complete clinical and radiological resolution with non-neurosurgical management—A case report - Mei Qi; Yaqing Zeng; Bofu Ruan; Qin Wang (Frontiers in Medicine, 2026)
Background Streptococcus suis ( S. suis ) meningitis is a severe zoonotic central nervous system infection, with permanent sensorineural hearing loss as its most common long-term sequela. Hydrocephalus is an extremely rare and underrecognized complication of S. suis meningitis, and no case of communicating hydrocephalus secondary to S. suis meningitis managed successfully with non-neurosurgical therapy has been formally documented. Case presentation A 52-year-old man presented with 8 days of progressive dizziness and gait imbalance. Contrast-enhanced magnetic resonance imaging (MRI) confirmed communicating hydrocephalus with diffuse leptomeningeal enhancement and no ventricular obstruction. Cerebrospinal fluid (CSF) cultures remained persistently negative, while metagenomic next-generation sequencing (mNGS) identified S. suis within 48 h with a relative abundance of 92.60%. Guideline-recommended targeted antimicrobial therapy combined with short-course adjunctive dexamethasone achieved complete clinical and radiological resolution without neurosurgical intervention. The patient remained asymptomatic with intact bilateral hearing at the 10-month follow-up. Conclusion To our knowledge, this is the first reported case of S. suis meningitis-associated communicating hydrocephalus successfully managed without neurosurgery. Accurate hydrocephalus subtyping via contrast-enhanced MRI and rapid pathogen identification via mNGS may help inform clinical decision-making regarding the potential for non-neurosurgical management in carefully selected patients.